Cold case report: Geoforensic brownfield site search for murder victim based on prison informant lead - Jamie K. Pringle; Andrew Binley; Kristopher D. Wisniewski; Ben Davenward; Vivienne G. Heaton; Georgina E. Handley (Forensic Science International: Reports)
Cold case searches for the missing can be challenging, especially when the convicted perpetrator may or may not be giving forensic investigators truthful information. This paper reports on a cold case search for a teenage girl who was reported missing during the mid-2000s in north-west England, with this being the second area searched following the disclosure of information by a suspect prison cellmate. The disused search area had many uses, including an animal sanctuary after the girl went missing. Initial police ground searches proved unsuccessful in locating the victim. Geoforensic search aims was to use geophysics to identify potential burial position(s) within the search site priority areas to be then forensically investigated. A multi-phased geoforensic search was conducted, initially forensic botany removed vegetation back to when the girl went missing, electromagnetic induction (EMI) surveys then identified potential burial areas, before ground penetrating radar (GPR) surveys were also collected in other areas to identify near-surface buried object positions. The EMI and GPR identified priority targets were then forensically excavated, with several isolated animal burials recovered and a drainage pipe identified to be cause of other geophysical targets, which gave confidence that any burials onsite could be identified geophysically. No case-relevant material was found. The case presented suggests these geoforensic approaches provide assurances to rule out forensic search locations, saving time and costs in such cold case investigations.